Can academic performance enhance group membership and leadership among student entrepreneurs in Malaysia? - Isidore Ekpe; Norsiah Mat (Canadian Center of Science and Education, 2016)
This study examined the effect of academic performance on social group membership and future leadership among student entrepreneurs in Malaysia so as to enhance good quality leaders in the future. Underpinned to Blau’s social exchange theory, the study adopted survey method and proportionate stratified random sampling to collect data from 319 semester-5 university students from three public universities in Malaysia. Data analysis was done through descriptive statistics and regression methods. We found that high academic performance significantly and positively influenced future leadership among Malaysian student entrepreneurs. Therefore, the government and the universities management should initiate more advocacy programs to counsel students on the need to focus on their studies so as to earn better grades which would enhance their active participation in leadership activities after school. However, there was no evidence to prove that academic performance had any influence on group membership among the student entrepreneurs. The study was limited to university business students. Similar studies could be conducted on youths in other academic institutions such as secondary schools.